Bezpośrednie inwestycje zagraniczne a rynek pracy w Polsce - Rymarczyk, Jan; Rymarczyk, Jerzy (Foreign Direct Investment and the Labor Market in Poland, 2006)
Since the beginning of the system transformation in Poland influx of the foreign capital in the form of direct foreign investment (FDI) has been very dynamic. The year 2000 witnessed the highest value of the inflow - more than USD 10 billion; however the foreign investment in the following years was significantly lower, at the rate of about USD 6.5 billion in 2003 which was the result of weakening privatization processes and general negative aspects of economy in the world trade. All in all the aggregate FDI, according to the Polish Information Foreign Inwestment Agency, was c. USD 73 billion and Poland ranked first among the countries in its region in this respect. The transition from the centrally managed economy to the free market economy was also related to the rationalization of employment and the change of the free market economy was also related to the rationalization of employment and the change of the hidden unemployment to recorded (visible). Demographic and trend economic factors also had a significant influence on the rate of unemployment in Poland, which reached the highest level among the OECD countries. The rate of unemployment would probably have been even higher if there had not been so much foreign investment in the form of FDI. It is estimated that foreign capital companies and enterprises give jobs to over 1 million people in Poland, i.e. every fifth person is employed there. It seems that in the near future the unemployment rate will decrease in Poland. This will be influenced by our membership in the EU, as well as by better economic trends and further influx of FDI.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1138, s. 90-102